Aerobic Solid State Red Phosphorescence from Benzobismole Monomers and Patternable Self‐Assembled Block Copolymers. Issue 45 (9th October 2018) - Parke, Sarah M.; Hupf, Emanuel; Matharu, Gunwant K.; de Aguiar, Inara; Xu, Letian; Yu, Haoyang; Boone, Michael P.; de Souza, Gabriel L. C.; McDonald, Robert; Ferguson, Michael J.; He, Gang; Brown, Alex; et al.
Abstract: The synthesis of the first bismuth‐containing macromolecules that exhibit phosphorescence in the solid state and in the presence of oxygen is reported. These red emissive high molecular weight polymers (>300 kDa) feature benzobismoles appended to a hydrocarbon scaffold, and were built via an efficient ring‐opening metathesis (ROMP) protocol. Moreover, our general procedure readily allows for the formation of cross‐linked networks and block copolymers. Attaining stable red phosphorescence with non‐toxic elements remains a challenge and, thus, our new class of soluble (processable) polymeric phosphor is of great interest. Furthermore, the formation of bismuth‐rich cores within organic–inorganic block copolymer spherical micelles is possible, leading to patterned arrays of bismuth in the film state. Abstract : Turning on Bismuth : The synthesis of red and orange emitting bismuth‐based phosphors is reported. The modular synthetic approach allows for rapid ring‐opening metathesis polymerization to yield block copolymer spherical micelles that assemble into organized films with bismuth‐rich, metallized domains.